Rosa Luxemburg Band 1: Leben und Wirken - Jacob, Frank; Scharenberg, Albert; Schütrumpf, Jörn (Büchner-Verlag, 2021)
Rosa Luxemburg was one of the most important intellectuals of the »long« 19th century, and her work in politics and within the European labor movement was extremely manifold. She understood socialism - especially to the displeasure of the Bolsheviks - as a unity of political and social freedoms. For this reason, she remains a figure of identification to this day, and her writings have an unbroken relevance. Luxemburg's multifaceted life spanned from the birth of the German Empire to shortly after its end (1871-1919) and will be honored in a two-volume edition in the anniversary year 2021. Volume 1 provides an overview of her biography and takes stock of her political activities.